Shelf life of ground meat marketed in the Municipality of Boa Vista – Roraima (Research, Society and Development, 2021)
Beef is consumed all over the world, but according to its own characteristics (physical, chemical and biological) they can undergo marked deterioration processes, as well as being carriers of deteriorating and or pathogenic organisms. From this, the objective of this work was to determine the shelf life of ground meat sold in hypermarkets and markets in the municipality of Boa Vista-RR, through sensory analysis, pH and contamination indicators: aerobic mesophilic microorganisms and psychrotrophic aerobes. The analyzes were performed at the Animal Products Laboratory at the Federal University of Roraima. Sensory analysis was performed according to characteristics visualized during the product's storage, the pH was determined by means of a pH meter and count of microorganisms. From the obtained results, the useful life of the ground meat in relation to the sensorial analyzes was around seven days. What it says about the microbiological quality of ground meat, according to Brazilian legislation, the meat was fit for consumption until the tenth day of storage, with counts of mesophilic and psychrotrophic bacteria, respectively, around 4.3 x 10⁵ UFC/25g and 4.4 x 10⁵ UFC/25g. As for the pH values of the meat, they were in compliance with current Brazilian legislation, only on the first day of storage. However, further studies are needed in the region regarding the quality of ground beef, which when compromised, can pose dangers to Public Health.